간호대학생이 지각한 문화 역량과 간호사 자질 중요도와의 관계 - 최경숙(Kyung Sook Choi); 이우숙(Woo Sook Lee); 박연숙(Yeon Suk Park); 전명희(Myunghee Jun); 이소영(So Young Lee); 박연우(Yeonwoo Park); 박수영(Soo Young Park); Vipavee, Thongpriwan (지역사회간호학회지, 2016)
Purpose: This study was conducted to investigate the relationship between cultural competency and the importance of nurses' qualities perceived by undergraduate nursing students. Methods: Researchers developed two tools for this study after reviewing the related literature and conducting research team workshops: questionnaire of cultural competency and the importance of nurses' qualities. 200 nursing students were recruited in convenient sampling to respond to these questionnaires. Of nurses' 10 qualities, major affecting factors on the cultural competency were identified by stepwise multiple regression analysis. Results: The nursing students perceived technical nursing skills and professional nursing knowledge as nurses' most important qualities. However, 'having a passion for patient care', 'demonstrating strong nursing profession's code of ethics' and 'teaching and research ability' were found as significant influencing factors on the variance of the cultural competency. These three factors explained 16% of the total variances of the cultural competency (F=13.98, p<.001). Conclusion: The educational strategies to improve cultural nursing competency need to incorporate students' expectations for the professional nurses' roles. Also, further studies need to develop reliable and valid measurement tools for cultural competency.